2014
DOI: 10.1111/aab.12181
|View full text |Cite
|
Sign up to set email alerts
|

Threshold values of canopy reflectance indices and chlorophyll meter readings for optimal nitrogen nutrition of tomato

Abstract: Sustainable and optimal economic N management requires correct and timely on-farm assessment of crop N status to detect N deficiency or excess. Optical sensors are promising tools to assess crop N status throughout a crop or at critical times. The ability of optical sensor measurements of canopy reflectance (Crop Circle ACS 470) and leaf chlorophyll (SPAD 502 chlorophyll meter) to assess crop N status was evaluated weekly throughout an indeterminate tomato crop. Strong linear relationships with the optical sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 51 publications
5
61
3
4
Order By: Relevance
“…Existe una clara correlación entre las unidades SPAD (Análisis del Desarrollo de la Planta en el Suelo, por sus siglas del inglés Soil Plant Analysis Development) y la concentración de clorofila y nitrógeno total en las hojas de tomate, según autores como Rodríguez et al (1998), Padilla et al (2014), Camen et al (2017). Los valores SPAD se obtienen en función del principio que considera que parte de la luz que llega a la hoja es absorbida por la clorofila y la parte que se refleja entra en contacto con la celda SPAD-502 (Minolta Camera Co.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Existe una clara correlación entre las unidades SPAD (Análisis del Desarrollo de la Planta en el Suelo, por sus siglas del inglés Soil Plant Analysis Development) y la concentración de clorofila y nitrógeno total en las hojas de tomate, según autores como Rodríguez et al (1998), Padilla et al (2014), Camen et al (2017). Los valores SPAD se obtienen en función del principio que considera que parte de la luz que llega a la hoja es absorbida por la clorofila y la parte que se refleja entra en contacto con la celda SPAD-502 (Minolta Camera Co.…”
Section: Introductionunclassified
“…El contenido de clorofila y absorción de nitrógeno se han correlacionado con las unidades SPAD en diversas condiciones ambientales en gramíneas (Hidema et al, 1992;Piekielek y Fox, 1992), con distintos sustratos y aportes nutricionales en tomate (Rodríguez et al, 1998) y según la tolerancia de distintos híbridos de tomate al estrés salino (Camen et al, 2017). Autores como Wood et al (1992) y Padilla et al (2014), indican que el SPAD-502 permite hacer seguimiento al contenido de nitrógeno y clorofila durante el desarrollo del cultivo lo que facilita el manejo nutricional de la planta. Rodríguez et al (1998), concluye que el estado fenológico del cultivo afecta el valor de las unidades SPAD lo que puede explicarse por la actividad fisiología de la hoja que varía en el tiempo y tiene directa relación con el color de la hoja desde su emergencia a la senescencia.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The SPAD produces a dimensionless index positively correlated to the concentration of chlorophyll in the leaf blade, which is in turn related to the concentration of N in plant tissues. Once the values of N sufficiency are assessed, the corresponding SPAD index value can be used to support N fertilization [104][105][106][107]. Some authors have found variability in the SPAD index when the culture was carried out in the presence of abiotic stress [106].…”
Section: Plant Monitoringmentioning
confidence: 99%
“…Petiole sap testing involves taking leaf petioles and collecting the sap, which is then tested for nitrate and/or potassium using portable meters [119]. Chlorophyll meters are used to measure the "greenness" of individual leaves and to monitor nitrogen status after proper calibration against the crop with proper fertilization [120,121]. Monitoring the soil N status by collecting soil samples, or placing suction cups beyond the root system to collect soil solution, also constitute efficient mitigation practices, as they provide information regarding the N stored in the soil and/or moving beyond the roots' depth.…”
Section: Fertilizer Managementmentioning
confidence: 99%